Correction: Biocompatible nitrogen-doped carbon dots: synthesis, characterization, and application. Issue 42 (22nd October 2020) - Park, Yoonsang; Kim, Yujin; Chang, Heemin; Won, Sungyeon; Kim, Hyemin; Kwon, Woosung
Abstract : Correction for 'Biocompatible nitrogen-doped carbon dots: synthesis, characterization, and application' by Yoonsang Park et al., J. Mater. Chem. B, 2020, DOI: ; 10.1039/d0tb01334j .